Investigating the Plights of Nigerians in Diaspora: A Case Study of Nigerians Studying in Malaysian Universities - YUSUF SULEIMAN; KAWULEY MIKAIL IBRAHIM (Indonesian Research Journal in Education |IRJE|, 2020)
In view of researchers’ personal experiences and report on numerous problems of Nigerians in diaspora, this study investigates the plights of Nigerians in diaspora with specific focus on Nigerians studying in Malaysian universities. In order to select participants for the study stratified, purposive and convenience sampling techniques were used to select 10 Nigerian students from three Malaysian universities, namely Universiti Utara Malaysia (UUM), Universiti Malaya (UM) and Insaniah University College. Instrument used to collect data from the participants include interview and observation. Specifically, observation method was used to complement the interviews findings. Our findings revealed that Nigerians are faced with numerous challenges, which include apathetic attitude of Nigerian embassy in Malaysia, lack of part-time job opportunities, high exchange rate and visa issue. Also, our findings suggest solutions to the problems of Nigerians in Malaysia. They include quick response to students’ challenges by the Nigerian embassy, availability of part-time job opportunities for Nigerians and other international students and issuance of 2 years visa. The study recommends that Nigerian embassy in Malaysia should have a comprehensive list of Nigerians schooling in various Malaysian institutions with a view to enable them to have an accurate data of their citizens. By doing so, the embassy will be able to use the data to attend to students’ requests at all times.